PTU-130 Efficacy of serology-based diagnosis for coeliac disease in children in a tertiary UK centre. (8th June 2018) - Rao, Arati; Lorentzen, Betina; Vadamalayan, Babu; Deheragoda, Maesha; Thangarajah, Anthi; Hope, Ben
Abstract : Introduction: ESPGHAN published guidelines in 2012 allowing for non-tissue diagnosis of coeliac disease (CD) in symptomatic children with high levels of circulating tissue transglutaminase antibodies (TTG), anti-endomysial antibodies (EMA) and positivity of HLA-DQ2 or DQ8. This is contrary to adult guidelines, where histological diagnosis is recommended. This study assessed the use and effectiveness of non-tissue diagnosis in a tertiary centre. Methods: A retrospective review of all children (age <18 years) in a single centre newly diagnosed with CD between 1/2/12 to 31/12/16 with 1 year follow up. If endoscopy was performed, 2 biopsies were taken from the duodenal cap and 4 from D2 or lower, as per protocol. Histology was analysed using the modified Marsh grading system. Data were collected using electronic patient records. Analysis was performed using SPSS version 21 (Chicago, USA). Significance was defined as p<0.05. Results: Of 82 newly diagnosed patients, 12 were asymptomatic children identified via screening and therefore excluded, leaving a cohort of 70. 61% (n=43) were female. Median age at diagnosis was 7.58 years (range 0.86–17.66). The commonest presenting symptom was abdominal pain, with over 50% of patients affected. All had TTG measured at baseline, with a mean[SD] of 88.0 [46.6] U/ml, 7 being the upper limit of normal (ULN) and 128 the maximum recorded with our assay. 35.7% (n=25) had a TTG <10 times ULN. These children all had endoscopy, as per ESPGHAN guidelines. Overall, 76% (n=53) were diagnosed by endoscopy and biopsy. No patients had concomitant pathology diagnosed and there were no operative complications. 47% (n=33) had complete serological testing; 34% (n=24) fulfilled ESPGHAN serological diagnostic criteria. 24% (n=17) were given a diagnosis of CD without small bowel biopsies (figure 1). 75% of patients (n=8) who met the criteria were offered non-biopsy diagnosis and all, but one preferred this option. At maximum follow up, none of the patients diagnosed serologically have required endoscopy. There was a significant fall in TTG from baseline (mean 87.3, SD 46.5) at 6 months (mean 23.5, SD 29.7; p=0.003) and at 12 months (mean 12.5, SD 22.1; p=0.017). This decrease was significantly greater in children diagnosed serologically both at 6 months (mean [SD] 82.8 [42.0] vs 57.6 [43.6]; p=0.04), and at 12 months (mean [SD] 93.0 [41.2] vs 67.4 [45.6]; p=0.049). Conclusions: Serology based confirmation of CD proved to be both effective and appealing to our patient population. The results should encourage greater uptake of this diagnostic strategy. Small bowel biopsies remain important in children with suggestive symptoms but whose TTG titres are <10 times the ULN, or in whom there is concern about dual pathology.